In Vitro Effect of Volatile Substances from Eucalyptus Oils on Rhipicephalus microplus - Rodrigues, Leandro; Giglioti, Rodrigo; Gomes, Ana Carolina Peroni; Katiki, Luciana Morita; Otsuk, Ivani Pozar; Silva Matos, Renata da [UNESP]; Nodari, Elen Fernanda [UNESP]; Verissimo, Cecilia Jose (Springer, 2020)
Volatile oils have been extensively investigated as an alternative for tick control. This study evaluated thein vitroeffects of volatile compounds emanated byCorymbia citriodora(Hook.) K.D.Hill & L.A.S.Johnson andEucalyptus globulusLabill., Myrtaceae, volatile oils and their major compounds, citronellal and 1,8-cineole, respectively, at doses of 10, 20, 40, 60, 80 and 100 mg/g, onRhipicephalus micropluslarvae and engorged females. The effects of these volatile oils were compared with those of commercial acaricides. In bioassays with engorged females, percentages of oviposition inhibition (OI %) and efficacy of the product (EP %) were determined, as well as tick larval mortality. The larval tests with citronellal presented high mortalities (> 80%) for all analysed doses, except 10 mg/g, while those for 1,8-cineole at the lowest dose (10 and 20 mg/g) produced the highest mortality (> 85%). In general, the volatile compounds released by these oils resulted in larval mortality and inhibition of the reproductive parameters in the engorged females, with efficacies over 80%.
Keywords: Acaricidal activity; Volatile oils; Alternative control; Ticks